Difference in clinical crown length of maxillary central incisors and gingival display at rest and during smiling based on gender - Zaini, Nadia Atina; Rikmasari, Rasmi; Damayanti, Lisda (Padjadjaran Journal of Dentistry, 2013)
Introduction: The aim of the present study was to investigate the effect of gender on the degree of maxillary central incisors and associated gingival display when the lips are at rest and during smiling. Methods: A total of 65 subjects (40 females [61.5%]; 25 males [38.5%]) of Malaysian Malay community studied in UNPAD were included in the study. All of the subjects had all natural anterior teeth present with no caries, extreme occlusal wear, restorations, extrusion, obvious deformities, or tooth mobility. The visible portions of the maxillary central incisor, and associated gingival at rest and smiling were measured vertically from the lower border of the upper lip to the incisal edge of the incisors. The measurements were measured using an electronic digital caliper and repeated three times. The mean value was calculated and statistical analyses were performed by Student t test. Results: Outcome of the study indicated that there is marked difference statistically (p < 0.05) with the clinical crown length display at rest (CCLR). However, the clinical crown length display during smiling (CCLS) and gingival display during smiling (GD) differences is non significant (p > 0.05) between these two genders. Conclussion: Females displayed more clinical crown length of maxillary central incisors than males at rest. During smiling, no gender differences in maxillary central incisors display were recorded, however, females displayed more maxillary gingival than males.